Wspieranie rozwoju uczniów w integracyjnej i inkluzyjnej edukacji wczesnoszkolnej - Dobrowolski, Tomasz (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Pupils attending to integration classes or participating in inclusive education at the early childhood education level have many needs in their development sphere. The solutions, which are currently available, as a form of help, not always meet the comprehensive development of a child with special educational needs. It is worth to take a look precisely what is the difference between integration and inclusion, as well as the offer educational supporting children with deficiency in these institutions.
Keywords: early childhood education; inclusive; integration; supporting pupil